Potential mechanisms of cellular injury following exposure to a physiologically relevant species of inorganic mercury. (April 2019) - Orr, Sarah E.; Barnes, Mary C.; Joshee, Lucy; Uchakina, Olga; McKallip, Robert J.; Bridges, Christy C.
Highlights: Cys- S -Hg- S -Cys causes oxidative injury, calcium dysregulation, and autophagy. Cys- S -Hg- S -Cys alters the cytoskeleton and leads to cell shrinkage. Necroptosis and necrosis are primary mechanisms for cell death following Hg exposure. Abstract: Mercury is a toxic metal that is found ubiquitously in the environment. Humans are exposed to different forms of mercury via ingestion, inhalation, and/or dermal absorption. Following exposure, mercuric ions may gain access to target cells and subsequently lead to cellular intoxication. The mechanisms by which mercury accumulation leads to cellular injury and death are not understood fully. Therefore, purpose of this study was to identify the specific intracellular mechanisms that are altered by exposure to inorganic mercury (Hg 2+ ). Normal rat kidney (NRK) cells were exposed to a physiologically relevant form of Hg 2+, as a conjugate of cysteine (10 μM or 50 μM). Alterations in oxidative stress were estimated by measuring lipid peroxidation and mitochondrial oxidative stress. Alterations in actin and tubulin were measured using specific fluorescent dyes. Calcium levels were measured using Fluo-3 AM Calcium Indicator while autophagy was identified with Premo ™ Autophagy Sensor LC3B-GFP. The current findings show that exposure to Hg 2+ leads to enhanced oxidative stress, alterations in cytoskeletal structure, increases in intracellular calcium, and enhanced autophagy. We have established a more complete understanding of intoxication and cellular injury induced by a relevant form of Hg 2+ in proximal tubule cells.